Atletika za otroke - Dekleva, Marina (Šport (Ljubljana), 2019)
The paper focuses on athletics for children which takes place in a relaxed atmosphere and in an elementary and stimulating manner. The athletics programme is managed by a teacher or coach who knows and understands the nature of child development and organises exercises according to the development stage of children. The programme utilises different forms of learning and methods of work and also includes suitable sports requisites that add variety to exercises. Competition should be an integral part of athletics and organised in a relaxed and fun way.
Keywords: athletics; atletika; children; games; igra; otroci; sport; šport